Acute Adrenal Insufficiency Associated with Tuberculous Vertebral Osteomyelitis and Lymphadenopathy: Case Report. (9th May 2012) - Anaforoğlu, İnan; Algün, Ekrem; İnceçayır, Ömer; Şiviloğlu, Çiğdem; Caymaz, İsmail
Abstract : A 51-year-old man developed anorexia, dizziness, nausea, vomiting, and weight loss. He had orthostatic hypotension, hyponatremia, hyperkalemia, and hypocortisolemia, and the diagnosis of adrenal insufficiency was made. Magnetic resonance imaging (MRI) showed asymmetrically enlarged adrenal glands. Biopsy of a hypoechoic, enlarged, inguinal lymph node showed caseating granulomas. Lumbar MRI showed vertebral body height loss and abnormal signal in L1 and L2; vertebral biopsy showed chronic, necrotic, caseating granulomatous inflammation consistent with tuberculous osteomyelitis. Clinical improvement occurred with isoniazid, rifampicin, pyrazinamide, and corticosteroids. The differential diagnosis of adrenal insufficiency should include tuberculosis, especially in geographic regions where tuberculosis is endemic.